Exploring serotonin-gated ion channels through repurposing strategies - Rodriguez Araujo, Noelia (2023)
A drug repurposing strategy that considers the chemical structure and molecular action on serotonergic Cys-loop receptors offers valu- able guidance for the rational reuse of existing drugs, thereby reduc- ing the time and costs associated with developing new medications. We focused on nematode and vertebrate 5-HT-gated ion channels and tested several drugs in clinical use using electrophysiological techniques. In nematodes, a unique serotonin-activated chloride channel, MOD-1, is emerging as a new target for antiparasitic drugs. In humans, 5-HT3A is involved in emesis and is an important player in the enteric nervous system. We previously demonstrated that tryptamine and its derivatives could be good candidates for anthelmintic therapy, acting on the serotonin MOD-1 receptor. We found that sumatriptan and eletriptan, from the triptan family, inhibit 5-HT-induced currents of MOD-1 receptor in a concentration-de- pendent manner. By using the nematode Caenorhabditis elegans, we revealed the anthelmintic actions of sumatriptan and eletriptan at the behavioral level. Our locomotor activity assays showed that both drugs produced a decrease in worms’ activity, with eletriptan being more potent than sumatriptan. Mutants lacking MOD-1 were partially resistant to both drugs. Also, we revealed novel aspects of MOD-1 function from the molecular level to the organism level, which may contribute to provide new directions for anthelmintic drug discovery and drug repurposing. By electrophysiology techniques we revealed that the anthelmintic piperazine (PZE), which acts at nematode GABA and MOD-1 receptors, decreased human 5-HT3A macroscopic currents elicited by 5-HT. The analysis showed that PZE acts as a negative allosteric modulator; thus PZE or its deriv- atives may be explored as promising therapeutic tools that may re- place classical orthosteric antagonists. Our drug repurposing strat- egy contributes to identify new targets and potential uses of drugs on a rational basis